My Archaeological Universities - Nina A. Kokorina (Археология евразийских степей, 2022)
The author recalls his journey into archaeology. Its beginning is connected with the circle of archaeologists at the State Museum of the Tatar ASSR and its head E.A. Khalikova. Further steps of entering science took place in the student archaeological circle of Kazan University and in the team of archaeologists of the Institute of Language, Literature and History named after G. Ibragimov of the Kazan branch of the USSR Academy of Sciences. The author notes the role of the first expeditions in choosing a profession, and then scientific issues, tells about the activities of the circle of archaeologists of the State Museum of Tatar Republic and the student archaeological circle of Kazan University in the 1960s and 1970s. The key role in the activities of these circles belonged to Kazan archaeologists of the 1960s and 1970s – E.A. Khalikova and A.Kh. Khalikov, as well as archaeologists of the Institute of Language, Literature and History of the Kazan branch of the USSR Academy of Sciences – T.A. Khlebnikova, P.N. Starostin, E.P. Kazakov, R.S. Gabyashev, etc.